Peristiwa Perebutan Pangkalan Udara Gorda di Cikande Tahun 1945 (Universitas Pendidikan Ganesha, 2022)
This study aims to describe the seizure of the Gorda Air Base in Cikande in 1945. The method used in this study is the historical method, including heuristics (source collection), source criticism, interpretation and historiography. The theory used in this research is the theory of Collective Action proposed by Charles Tilly. The results showed that in response to the news of Independence Indonesia that arrived in Banten, the Banten fighters carried out a power struggle and expelled Japanese soldiers from Banten. One of the seizure events occurred at Gorda Air Base. The seizure of Gorda Air Base ended well thanks to the collective and structured actions of the People's Security Agency (BKR) and the Special Police. Gorda Air Base functioned as a secret base, this base had an important role in Japanese air defense in Banten. The impact of the seizure of the Gorda Air Base added to the BKR obtained from the Gorda Air Base and was used to expel the Japanese from Banten. When the Gorda Air Base was taken over, it was used for flight training for Indonesian air fighters at the beginning of independence. The seizure of the Gorda Air Base was a brief event, but it had a significant impact on the struggle to seize and defend the Proclamation of Independence in Banten.